2010
DOI: 10.1007/978-3-642-13446-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Naïve Security in a Wi-Fi World

Abstract: Despite nearly ubiquitous access to wireless networks, many users still engage in risky behaviors, make bad choices, or are seemingly indifferent to the concerns that security and privacy researchers work diligently to address. At present, research on user attitudes toward security and privacy on public Wi-Fi networks is rare. This paper explores Wi-Fi security and privacy by analyzing users' current actions and reluctance to change. Through interviews and concrete demonstrations of vulnerability, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Swanson et al [37] offered another explanation. Their participants said they used public Wi-Fi because, despite awareness of certain risks, they did not believe the risks would be realised.…”
Section: B Factors Affecting a User's Decision To Use Public Wi-fimentioning
confidence: 99%
See 1 more Smart Citation
“…Swanson et al [37] offered another explanation. Their participants said they used public Wi-Fi because, despite awareness of certain risks, they did not believe the risks would be realised.…”
Section: B Factors Affecting a User's Decision To Use Public Wi-fimentioning
confidence: 99%
“…One study argued that users of public Wi-Fi networks were not aware of the risk [19]. Others show that users were aware of the risks but did not think the risks would be realised ( [30], [37], [21]). Sombatruang et al [33] did not statistically test this factor either and so we did and found that it did not significantly affect the decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…A study from 2010 by Swanson et al [11] reported on the perception of privacy and security when using wireless networks for a group of 11 randomly selected persons. They show that users make security choices based on (often mistaken) analogies to the physical world, similar to what happens in naïve, or "folk" physics, and that this leads to users who are confident in their knowledge about security while making unsafe decisions.…”
Section: Related Workmentioning
confidence: 99%
“…Many people use public Wi-Fi because it offers them utility. Swanson et al [38] found that -although users were aware of certain risks -they often do not believe the risk will be realised. Their study used a qualitative approach.…”
Section: Reasons For Using Public Wi-fimentioning
confidence: 99%
“…Our study provides empirical evidence that a significant proportion of participants' decisions about whether or not to connect to insecure public Wi-Fi network, are inconsistent with expected utility theory. This is an original piece of research exploring an aspect of decision-making not previously explored in studies investigating the decision-making process for using public Wi-Fi ( [16], [17], [18], [22], [28], [38], [47]) or in more general studies of expected utility theory [46]. Our results are in line with behavioural economics literature which argues that expected utility theory is inconsistent with the styles of decision-making that people actually adopt in many real-life choice situations [25].…”
Section: Rationale For Using Public Wi-fimentioning
confidence: 99%